Trees. Volume three, Three fates - Ellis, Warren (Image Comics, 2020)
The acclaimed TREES series, currently being adapted for television, returns with a brand new story of murder and ghosts. In the remote Russian village of Toska, there's a dead body by the leg of the Tree that landed eleven years ago. Police sergeant Klara Voranova, still haunted by that day, has no idea how this murder will change everything, nor what awaits her in the Tree's shadow.